2017
DOI: 10.1021/acsami.6b15168
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Photoelectrochemical Performance and Stability of Cu(In,Ga)Se2 Photocathode via TiO2-Coupled Buffer Layers

Abstract: We report on the photoelectrochemical (PEC) performance and stability of Cu(In,Ga)Se (CIGS)-based photocathodes for photocatalytic hydrogen evolution from water. Various functional overlayers, such as CdS, TiO, ZnSnO, and a combination of the aforementioned, were applied on the CIGS to improve the performance and stability. We identified that the insertion of TiO overlayer on p-CIGS/n-buffer layers significantly improves the PEC performance. A multilayered photocathode consisting of CIGS/CdS/TiO/Pt exhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Nam and Shin have concluded that the performance degradation of CuInGaSe 2 based photocathode was caused by the atomic redistribution of elements constituting the electrode. The TiO 2 ‐coated Zn x Sn y O z buffer layer performed better than TiO 2 ‐coated CdS in suppressing the degradation . These discussions suggest that the PEC performance and stability of photoelectrodes fabricated with PV‐grade semiconductor can be improved through careful design of their configuration.…”
Section: Semiconductors In Photoelectrochemistrymentioning
confidence: 99%
“…Nam and Shin have concluded that the performance degradation of CuInGaSe 2 based photocathode was caused by the atomic redistribution of elements constituting the electrode. The TiO 2 ‐coated Zn x Sn y O z buffer layer performed better than TiO 2 ‐coated CdS in suppressing the degradation . These discussions suggest that the PEC performance and stability of photoelectrodes fabricated with PV‐grade semiconductor can be improved through careful design of their configuration.…”
Section: Semiconductors In Photoelectrochemistrymentioning
confidence: 99%
“…Doing so on exible substrates can reduce device cost by enabling roll-to-roll fabrication and thus, facilitating technology implementation. 333 CIGS-CdS buried junctions have been adapted for water splitting 321,[334][335][336][337] (also on exible substrates 241 ), together with their earth-abundant equivalent CZTS. 240,335,[338][339][340][341] In 2 S 3 (ref.…”
Section: Buried Homojunctions To Maximize Efficiency and Cell Flexibilitymentioning
confidence: 99%
“…An electrocatalyst is a critical component of a PEC system and it is often bound on the surface of a light‐absorbing photoelectrode [2] . In the typical monolithic photoelectrode configuration, electrocatalysts are placed on the side where light is incident [3–5] . Therefore, not only catalytic activity but also light transmittance is an important factor to consider when designing an electrocatalyst‐coated photoelectrode system.…”
Section: Introductionmentioning
confidence: 99%
“…However, none has so far surpassed the catalytic activity of Pt. An obvious alternative approach is reducing the use of Pt, that is, improving the mass activity of Pt by forming a nanostructure with a high surface‐to‐volume ratio, such as nanoparticles, [5] nanowires, [20] patterned islands, [21] an atomic monolayer, [22] or even a collection of single atoms [23–25] . However, the past studies on forming nanostructured Pt encountered some issues such as inferior performance [26] and complex and/or harsh processing conditions [22] for the catalyst synthesis.…”
Section: Introductionmentioning
confidence: 99%